Outcomes of Revision Anterior Cruciate Ligament Surgery in Adolescents. Issue 6 (May 2019) - Ouillette, Ryan; Edmonds, Eric; Chambers, Henry; Bastrom, Tracey; Pennock, Andrew
Background: Although primary anterior cruciate ligament (ACL) reconstructions have been well studied in children and adolescents, the literature lacks information about revision ACL reconstructions in this population. Purpose: This study aims to analyze the outcomes of revision ACL surgeries in the pediatric population. Study Design: Case series; Level of evidence, 4. Methods: A retrospective study was performed on all revision ACL reconstructions performed at a single institution between 2009 and 2017. Patient demographic, injury, and operative data from both the initial surgery and the revision were documented. Outcome measures included the Lysholm score, Single Assessment Numeric Evaluation (SANE) score, Tegner activity score, visual analog scale for pain, Hospital for Special Surgery Pediatric Functional Activity Brief Scale score, patient satisfaction, ability to return to the same level of sport, and any additional injury and/or surgery. Outcomes of the revision surgeries were compared with our institution's outcome database of primary ACL reconstructions. Results: During the study period, 60 revision ACL reconstructions were performed in 57 patients. Of these patients, 84% (n = 48) were available for a minimum 2-year follow-up and a mean follow-up of 4.4 years. A greater number of meniscal tears and cartilage injuries were documented in the revision cohort. Compared with the primary cohort, the revision cohort had lower SANE scores, Lysholm scores, and satisfaction. Furthermore, the revision cohort had a higher rate of graft failure than the primary cohort (21% vs 9%, respectively; P = .015), and only 27% of revision patients returned to the same level of sport. In a comparison of revision procedures performed with autograft versus allograft tissue, the autograft patients had higher Lysholm scores than the allograft patients (91 vs 83, respectively; P = .045) and trended toward a lower failure rate (11% vs 27%, respectively; P = .199). Conclusion: Adolescent patients undergoing revision ACL reconstruction had more meniscal and cartilage abnormalities, poorer functional outcomes, and higher graft failure rates than patients undergoing primary ACL reconstructions. Additionally, revision procedures performed with allograft tissue resulted in lower Lysholm scores and a trend toward higher failure rates. When an ACL graft fails in a young patient, strong consideration should be given to using autograft tissue for the revision.